Language, Subjectivity and Alterity: Humour in Children’s Discourse - Del Ré, Alessandra [UNESP]; Mendonça, Marina Célia [UNESP] (Springer Nature, 2022)
This text intends to present some considerations about language and discrimination, using the children’s humouristic language to discuss it. Our starting point is the following question: what is the role of the other (alterity) in the constitution of subjectivity, in and through language? We discuss this issue as we consider a specific phenomenon: children’s humour. The results of the analysis of the scenes of interaction between parents and child reveal the importance of the other in the constitution of this subject’s subjectivity in and through language. It is in the family (microculture) that what the child does and says is interpreted by others, and even if they do not understand exactly what the child really means (we will never know for sure), it is not important. The essential thing is to give meaning to what the child says, to be a language partner, to be the “broad vision” and then to help the child to constitute his/her own subjectivity. In the case of humour, the role of this other is also essential because it is the other who will guide the child in what he/she should understand as humour and what people laugh at in that family: it is through the bond that is created between the self and the other that humour exists. Finally, we understand that it is necessary to consider that if we understand the importance of the other in the constitution of the self - whoever this other may be and whatever they may bring to the self - how can we ever get to the point in which discrimination occurs? If we consider the role of the interaction with this other in order to become who we are, how can we ever value or undervalue them?.
Keywords: Humour; Language acquisition; The other and the self